Empreendedorismo feminino: o caso do Crediamigo no Vale do Jequitinhonha - MG - Cristiana Lara Cunha (2017)
The reality of Brazilian women, particularly low-income ones, in addition to the moments of crisis and financial instability experienced by the entire population in the current periods, evidences the need for an instrument that enables improvements in both financial and social spheres. It is through self-employment and the creation of microenterprises that a large part of the population can see a possibility of a better future and out of the condition in which they find themselves. In order to create these microenterprises, however, it is necessary to have credit, more precisely here through the figure of microcredit. This study, carried out with microentrepreneurs of Crediamigo, clients in the city of Diamantina ( and adjacencies), located in Vale do Jequitinhonha-MG, addresses issues of entrepreneurship, gender, credit and poverty, as well as empowerment related to women's access to microcredit. Its objective is to evaluate how microcredit influences microenterprises generated by women in Vale do Jequitinhonh. To do so, we use both quantitative and qualitative research techniques, seeking to obtain more complete results than if we performed with only one of the techniques. Thus, a descriptive analysis is used for the analysis of the questionnaires applied to the Survey, followed by clusters, searching for clusters according to the similarities observed in them. For the part of the semi-structured interviews, the content analysis is carried out in order to complement and validate the data obtained in the previous stage. The results show that the social class of the clients surveyed differs from the public to whom the microcredit is directed. Negative relation between the loan and the power of hiring of employees is also observed. And, mainly, it is observed that, although the use of credit is focused for the enterprise, there is still a deviation from purpose, since the use of credit for personal questions is recurrent.